ACCLIMATIZATING TECHNIQUES OF TOMATO ANEMONEFISH (AMPHIPRION FRENATUS BREVOORT, 1856) BROOD STOCKS - Loc, Ha Le Thi; Van, Phan Thi Hong (Vietnam Journal of Marine Science and Technology, 2009)
Tomato Anemonefish (Amphiprion frenatus) brood stocks from the wild were able to adapt and breed in capture condition. The results from experiments showed that temperature, salinity and presence of Magnificent Sea Anemone (Heteractis magnifica) closely related to ability of spawning, re-spawning of the brood stocks as well as egg adhesion to collectors. In stable condition of 26 0 C with the presence of the Magnificent Sea Anemone, at salinity of 33 - 35‰, the brood stocks started spawning after 51 days of acclimatization. The brood stocks spawned twice monthly in average and re-spawned after 3 to 5 days. Embryonic development on the collectors lasted 5 to 9 days. At salinity of 27 to 29‰, the re-spawning time lasted 5 to 9 days, the embryos were completely de-adhesive from the collectors after 9 days of spawning. At salinity of 40 to 42‰, the brood stocks stopped spawning.